Nitrates in complex angina management during the age of aggressive coronary atherosclerosis treatment - D. M. Aronov; V. P. Lupanov (Кардиоваскулярная терапия и профилактика)
The article focuses on differential treatment of stable angina patients. Effects of main antianginal and anti-ischemic medication groups are discussed. Clinical aspects of nitrate therapy in coronary heart disease (CHD) management are emphasized. Nitrates’ potential in treating various CHD forms is discussed.